Human APOBEC3B interacts with the heterogenous nuclear ribonucleoprotein A3 in cancer cells. Issue 8 (25th April 2018) - Mishra, Nawneet; Reddy, K Sony; Timilsina, Uddhav; Gaur, Deepak; Gaur, Ritu
Abstract: Human APOBEC3B (A3B), like other APOBEC3 members, is a cytosine deaminase which causes hypermutation of single stranded genome. Recent studies have shown that A3B is predominantly elevated in multiple cancer tissues and cell lines such as the bladder, cervix, lung, head and neck, and breast. Upregulation and activation of A3B in developing tumors can cause an unexpected cluster of mutations which promote cancer development and progression. The cellular proteins which facilitate A3B function through direct or indirect interactions remain largely unknown. In this study, we performed LC‐MS‐based proteomics to identify cellular proteins which coimmunoprecipitated with A3B. Our results indicated a specific interaction of A3B with hnRNP A3 (heterogeneous nuclear ribonucleoprotein). This interaction was verified by co‐immunoprecipitation and was found to be RNA‐dependent. Furthermore, A3B and hnRNP A3 colocalized as evident from immunofluorescence analysis. Abstract : Thirty‐seven unique proteins were found to interact with human APOBEC3B (A3B) that cluster into two interaction networks, the ribonucleoprotein complex and ribosomal‐associated proteins. Co‐immunoprecipitation followed by mass spectrometric analysis and confocal microscopy confirmed the interaction of A3B with the heterogeneous nuclear ribonucleoprotein (hnRNP A3). The A3B‐hnRNP A3 interaction was found to be mediated by RNA. Identification of A3B interacting proteins will provide useful insights into the mechanism of action of A3B in cancer cells.